The three-dimensional stable mandibular landmarks in patients between the ages of 12.5 and 17.1 years - Gui Chen; Mona Al Awadi; David William Chambers; Manuel O. Lagravère-Vich; Tianmin Xu; Heesoo Oh (BMC, 2020)
Abstract Background With the aid of implants, Björk identified two-dimensional mandibular stable structures in cephalograms during facial growth. However, we do not know what the three-dimensional stable structures are with certainty. The purpose of this study was to identify the most stable mandibular landmarks in growing patients using three-dimensional images. Methods The sample was comprised of two cone-beam computed tomography (CBCT) scans taken about 4.6 years apart in 20 growing patients between the ages of 12.5 (T1) and 17.1 years (T2). After head orientation, landmarks were located on the chin (Pog), internal symphysis (Points C, D and E), and mandibular canals, which included the mental foramina (MF and MFA) and mandibular foramina (MdF). The linear distance change between Point C and these landmarks was measured on each CBCT to test stability through time. The reliability of the suggested stable landmarks was also evaluated. Results The total distance changes between Point C and points D, E, Pog, MF, and MFA were all less than 1.0 mm from T1 to T2. The reliability measures of these landmarks, which were measured by the Cronbach alpha, were above 0.94 in all three dimensions for each landmark. From T1 to T2, the distance changes from Point C to the right and left mandibular foramina were 3.39 ± 3.29 mm and 3.03 ± 2.83 mm, respectively. Conclusions During a growth period that averaged 4.6 years, ranging from 11.2 to 19.8 years old, the structures that appeared relatively stable and could be used in mandibular regional superimpositions included Pog, landmarks on the inferior part of the internal symphysis, and the mental foramen. The centers of the mandibular foramina and the starting points of the mandibular canal underwent significant changes in the transverse and sagittal dimensions.